Poplarism - Lansbury, Edgar (London : Independent Labour Party)
1924 1924 1920s 8 pages local elections seriously ; having sent an enormous Labour majority to his Board of Guardians he expects that Board to do better work than the other kind of Board. He expects election promises to come true. SIR ALFRED MOND DOESN'T UNDERSTAND. Sir Alfred Mond could never understand this. No orthodox politician can. During our discussions with him at the Ministry he would say plaintively that he could not understand why our administration must differ so widely from that of the other Guardians of London. Our reply was quite simple. We were a Labour Board, elected to do certain work and to observe certain principles and a certain spirit in carrying out that work. POPLAR IS EFFICIENT. We resent the easy assumption that Poplar administration is lax, inefficient and wasteful. Consider the Electricity Department of the Council. Here is an undertaking where the £4 a week minimum wage for labourers is in operation ; yet the wages paid per unit produced, and the average price at which units are sold, are the lowest in the whole of London, private companies included. I quote below some figures, there being no room for the full table :— Average price per unit sold. d. Wage per unit. d. Poplar 1.474 0.06 Battersea 2.075 0.12 Fulham 2.862 0.21 London Electric Co. 1.807 0.14 Charing Cross Electric Co. 4.106 0.23 Chelsea Electric Co. 5.91 0.27 These figures relate to an Electricity Department which in a year's time will have laid cables in every street in the Borough. Now consider the work of the Poplar Public Health Department :— 1918. 1923. Death Rate in Poplar, per 1,000 22.7 11.3 Infantile Mortality, per 1,000 106.0 60.0 It will be seen that during the five years of Labour administration the general Death Rate and the rate of Infantile Mortality have been practically halved. The rate of Infantile Mortality is the lowest in the 95 largest towns in Great Britain. This is Poplarism in action. If we spend money it is to save life. This saving of life is the direct result of the work of the Guardians in giving relief to the destitute, and of the strenuous and successful work of the Council in supplying milk and nourishment to nursing and expectant mothers. 3 15X/2/209/47